Aplicación de las buenas prácticas de manufactura en la Asociación ASOPIFRUMA del Sur de Manabí - Moreira Guerrero, Jadira Kasandra (2023)
Good Manufacturing Practices (GMP) are basic principles and practices of hygiene, handling, preparation, packaging and storage of food intended for human consumption, to ensure that food is produced in adequate sanitary and hygienic conditions and minimize associated risks with production. The objective of this research was to develop a Manual of Good Manufacturing Practices (BPM) for the association of agricultural fruit producers (ASOPIFRUMA) in 24 de Mayo Canton, Noboa parish. In the first stage, a diagnosis and interview were carried out with the personnel in charge regarding compliance with BPM in relation to having a manual, in the second stage a plan of BPM activities was developed through instructions from the association's personnel, in addition microbiological analysis in relation to the provisions of INEN 2337:2008. The results showed that there is compliance in the diagnostic phase of 34%, which is not satisfactory, likewise there was no process manual, later the manual was prepared and its applicability was verified, achieving 60% compliance in relation to the above, in terms of microbiological analyzes, these showed an absence in the count of coliforms, molds and yeasts as established in the regulations described above. The application of the manual established in the productive activity of the association will ensure the quality of food and a responsible production system in accordance with the guidelines established in objective 12 of the 2030 agenda.